What Is the Arabic Verb for…? Guessing-Based Learning and Verb Retention among Malaysian Learners - Adham Hasif bin Najmuddin; Masnun Masnun (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
Arabic language education in Malaysia continues to develop in response to increasing demands for communicative competence and access to Islamic knowledge. However, many learners still struggle to recall basic Arabic verbs during spontaneous communication despite years of instruction. This study examines the effectiveness of guessing-based learning in improving Arabic verb retention among Malaysian learners. A classroom-based quasi-experimental mixed-methods design was employed, involving an experimental group exposed to structured guessing activities and a comparison group receiving conventional instruction. Quantitative data were collected through pre-tests and post-tests, while qualitative data were obtained from classroom observations and interviews. The findings reveal a statistically significant improvement in verb retention in the experimental group (p = .034, Cohen’s d = 0.38), whereas the comparison group showed no significant change. Qualitative results indicate increased learner attention, confidence, and engagement during learning activities. These findings suggest that guessing-based learning strengthens verb retention by activating cognitive effort and retrieval processes. This study concludes that guessing-based learning offers a practical and low-cost instructional strategy to support Arabic vocabulary acquisition and communicative competence in Malaysian Arabic education.